Sexual Assault Resource Availability on Texas Higher Education Campuses: A Web Site Content Analysis. Issue 5 (19th October 2016) - Franklin, Cortney A.; Jin, Hae Rim; Ashworth, Lindsay M.; Viada, Jane H.
Abstract : Sexual assault prevention and response remains a high priority for U.S. higher education institutions. Indeed, federal legislation and a recent White House task force have reiterated the importance of protecting college students from victimization during their tenure in postsecondary education. Informed by Eisenberg, Lechner, Frerich, Lust, and Garcia's (2012) content analysis, the current study uses a modified College Resources and Sexual Health (CRaSH) inventory to examine the status of 74 Uniform Crime Reports–reporting higher education institutions in Texas. Doing so assesses prevention, resources, response, and aftercare for victims of sexual assault. Findings demonstrate a primary reliance on target-hardening strategies, health clinics, and law enforcement responses, often to the neglect of advocacy, crisis intervention, and educational programs. Directions for research are discussed, and best practices in programming implementation to augment existing strategies are suggested.